2014
DOI: 10.1002/jclp.22134
|View full text |Cite
|
Sign up to set email alerts
|

Moral Injury, Meaning Making, and Mental Health in Returning Veterans

Abstract: These findings provide preliminary evidence that difficulties with meaning making could serve as a mediating pathway for how MIEs increase the risk for adjustment problems after warzone service, but that other factors associated with moral injury also have a bearing on psychological functioning among Veterans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
167
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(190 citation statements)
references
References 44 publications
16
167
2
Order By: Relevance
“…In conclusion, we feel it is important to further explore the concept of moral injury, as well as the relation between guilt and shame in military populations, and its implications for the onset, maintenance, and treatment of combat-related PTSD and other mental conditions (see also Currier et al, 2015;Yan, 2016). We reviewed and illustrated how guilt and shame can be drivers to chronicity in PTSD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, we feel it is important to further explore the concept of moral injury, as well as the relation between guilt and shame in military populations, and its implications for the onset, maintenance, and treatment of combat-related PTSD and other mental conditions (see also Currier et al, 2015;Yan, 2016). We reviewed and illustrated how guilt and shame can be drivers to chronicity in PTSD.…”
Section: Resultsmentioning
confidence: 99%
“…Inadequate measurement of combatrelated guilt may be one reason for this deficiency in the literature. Yet, despite some initial reports Campbell, 2016;Currier, Holland, & Malott, 2015), well validated instruments measuring moral injury are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Although research on morally injurious events is still in its infancy, it has been observed that not all morally injurious events meet PTSD's requirements for Criterion A traumatic events as given in the fifth edition of the DSM (i.e., DSM‐5 ; Litz & Kerig, ). Furthermore, early research suggests that although MI and PTSD are intertwined, they also appear to be distinct (Bryan, Bryan, Roberge, Leifker, & Rozek, ; Currier, McDermott, Farnsworth, & Borges, ), and that morally injurious events serve as a risk factor for a range of psychological difficulties, including suicidal ideation and behavior, depression, and substance use disorders (Battles et al., ; Bryan et al., ; Currier, Holland, & Mallot, ; Kelley et al., ; Maguen et al., ). Rather than pigeon‐holing MI to solely exist within the construct of PTSD and fear‐based biological models of posttraumatic stress, the functional contextual definition approaches MI transdiagnostically, making it applicable to a much wider range of clinical conditions.…”
Section: A Functional Contextual Definition Of Moral Injurymentioning
confidence: 99%
“…In addition to the potential impact of violations of one's moral code on functioning, MIEs have been established as a transdiagnostic risk factor for a range of psychological difficulties including posttraumatic stress disorder (PTSD), suicidal ideation and behavior, depression, and substance use (Battles et al, ; Bryan, Bryan, Roberge, Leifker, & Rosek, ; Currier, McDermott, Farnsworth, & Borges, ; Currier et al, ; Kelley, Braitman, White, & Ehlke, ; Maguen et al, ). The links between exposure to MIEs and the development of PTSD are particularly robust.…”
Section: Introductionmentioning
confidence: 99%
“…This suffering can be conceptualized as moral injury (Borges, 2019;Farnsworth, Borges, & Walser, 2019;Farnsworth et al, 2017). As evidence of the potential impact of moral injury on functioning, exposure to MIEs has been associated with relationship distress, spiritual disengagement, and workplace difficulties (Currier, Holland, & Mallot, 2014;Fontana & Rosenheck, 2004;Purcell, Koenig, Bosch, & Maguen, 2016).…”
Section: Introductionmentioning
confidence: 99%